2007
DOI: 10.1007/s00604-007-0866-0
|View full text |Cite
|
Sign up to set email alerts
|

Towards the identification of characteristic minor components from textiles dyed with weld (Reseda luteola L.) and those dyed with Mexican cochineal (Dactylopius coccus Costa)

Abstract: Towards the identification of characteristic minor components from textiles dyed with weld (Reseda luteola L.) and those dyed with Mexican cochineal (Dactylopius coccus Costa)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
62
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 19 publications
7
62
0
1
Order By: Relevance
“…Those components including their retention time (rt), their EC, their monoisotopic mass (m/z), the RDBeq and their major HRMS/MS fragments are listed in Table 2. Crossing those MS data (notably the parent ion and fragmentation patterns) with the literature [23,24], a number of flavones and flavonoid glycosides have tentatively been identified. However, the exact nature of some isomers could not be solved.…”
Section: Putative Identification Of Compoundsmentioning
confidence: 92%
See 1 more Smart Citation
“…Those components including their retention time (rt), their EC, their monoisotopic mass (m/z), the RDBeq and their major HRMS/MS fragments are listed in Table 2. Crossing those MS data (notably the parent ion and fragmentation patterns) with the literature [23,24], a number of flavones and flavonoid glycosides have tentatively been identified. However, the exact nature of some isomers could not be solved.…”
Section: Putative Identification Of Compoundsmentioning
confidence: 92%
“…This compound could hence correspond to 7-O-methylluteolin or to 3 -O-methylluteolin (also known as chrysoeriol), both have already been identified in R. luteola [24,29].…”
Section: Putative Identification Of Compoundsmentioning
confidence: 95%
“…Gıda, şekerleme, alkolsüz içecekler ve ilaçlar için renklendirme ajanı olarak kullanılan azo boyarmaddeleri, ürtiker ve astım bronşit gibi ani aşırı duyarlılık reaksiyonlarından sorumlu tutulmaktadır (8). Sentetik boyarmaddelerin birçoğunun toksik, kanserojen olması ve atıklarının çevre kirliliğine neden olması doğal boyarmaddeleri yeniden gündeme taşımış ve kullanımları; gıda, ilaç, kozmetik ve tekstil boyama endüstrisi alanında ivme kazanmıştır (9,10). Bazı flavonoid grubu boyarmaddelerin çeşitli metallerle yaptıkları kompleksler potansiyometrik ve spektrofotometrik olarak incelenmiştir (11)(12)(13)(14).…”
Section: öZetunclassified
“…11,14,15) The two isomers of CA were identified as 2-C-α-glucofuranoside and 2-C-β-glucofuranoside of kermesic acid (DCIV and DCVII, respectively). [14][15][16] Stathopoulou et al recently reported that DCIV and DCVII produce two isomeric forms via anomerization and both can be transformed to CA, 15) although the mechanism of inter-conversion has not been clarified. The time course of the transformation between CA, DCIV and DCVII has not yet been clarified.…”
mentioning
confidence: 99%
“…In addition, the minor components in food additives, colored textiles and historical artwork generally have been required to identify the species and the geographical origin of the cochineal by using multivariate statistical methods such as principal components analysis, partial-least squares discriminant analysis and hierarchical cluster analysis. 1,[6][7][8][9][10] The quality, insect species, and geographical origin of cochineal dye are typically evaluated using an HPLC equipped with a UV-Vis detector 6,7,11,12) and a photodiode array detector 1,[13][14][15] to determine carminic acid (CA), the main constituent of cochineal, as well as minor components.…”
mentioning
confidence: 99%